Prosocial behavior is related to later executive function during early childhood: A longitudinal study. Issue 3 (3rd May 2020) - Moriguchi, Yusuke; Shinohara, Ikuko; Todo, Naoya; Meng, Xianwei
ABSTRACT: Previous research has shown that executive function is correlated with prosocial behavior during early childhood. Whether early prosocial behaviors were associated with later executive function during preschool years or vice versa was thus examined in a longitudinal design. The prosocial behaviors and executive function of children ( N = 64) aged 42 to 65 months were evaluated twice (Times 1 and 2), based on teachers' reports and children's performance on hot and cool executive function tasks. Results revealed that prosocial behaviors at Time 1 were associated with later hot executive function at Time 2, but executive function at Time 1 was not related to prosocial behaviors at Time 2. These findings suggest that prosocial behaviors may enhance children's hot executive function.